The Clinical Impact of Substance Use in Schizophrenia: A Study in an Irish Population - Casey, Pádraig; Corvin, Aiden (Trinity Student Medical Journal, 2008)
Background: Substance use may be a risk factor for the onset of schizophrenia. However to date the impact of substance use in schizophrenia has not been fully explored in an Irish population. In this study we examine the clinical impact of substance use in schizophrenia within an Irish population. Methods: The study sample consisted of 159 participants with a diagnosis of schizophrenia who were recruited to the ongoing Resource for Psychoses Genomics Ireland Study. All participants were interviewed with the Structured Clinical Interview for Diagnostic Statistical Manual IV to confirm diagnosis. Information on age at onset, illness course and substance use was collected at this interview and from case note review. Results: In total, 48% of the participants reported lifetime substance use (including alcohol misuse). Cannabis was the most commonly used substance (82% of all users). Cannabis had an independent effect on the age at onset of psychosis, after adjusting for gender and use of substances other than cannabis. There was a trend towards more positive psychotic symptoms in substance users but it was not statistically significant. Conclusions: Our results confirm the high lifetime prevalence of substance use in schizophrenia. In addition, results show an earlier age at onset of illness in cannabis users. This provides further evidence for the association between cannabis use and onset of schizophrenia, although causality cannot be assumed.